Nutrient Intake, Morbidity and Nutritional Status of Preschool Children are Influenced by Agricultural and Dietary Diversity in Western Kenya - Walingo, M.K.; Ekesa, B.N. (Pakistan Journal of Nutrition, 2013)
A cross sectional survey was set up to assess the influence of agrobiodiversity and dietary diversity on morbidity, nutrient intake and the nutritional status of preschool children in Western Kenya. About 34.8% preschool children were severely stunted, 21.5% severely underweight and 8.3% were severely wasted. There was a positive and strong relationship between agricultural biodiversity, dietary diversity and caregivers’ level of education. Morbidity level and dietary diversity had significant influence on underweight levels and stunting. Consideration of agrobiodiversity in terms of dietary diversity can improve the nutrition and health status of a preschool child.